One year study of CT scan in patients with visual field loss (1990)
19 patients from the Neuro-Ophthalmology clinic of the Western Infirmary, were found during a one year period, to have various types of visual field loss and on the basis of this were sent for CT Scanning. 12 out of the 19 patients had positive CT Scans, the other 7 had no demonstrablepathology on CT Scan.